Study of the Potential Endocrine-Disrupting Effects of Phenylurea Compounds on Neurohypophysis Cells In Vitro - Krisztián Sepp; Zsolt Molnár; Anna M. László; Tünde Alapi; László Tóth; Andrea Serester; Zsuzsanna Valkusz; Márta Gálfi; Marianna Radács (International Journal of Endocrinology)
Homeostatic disruptor agents, and endocrine disruptor compounds (EDC) specifically, can originate from agricultural and industrial chemicals. If they modify the adaptation of living organisms as direct (e.g., by altering hormone regulation, membrane functions) and/or indirect (e.g., cell transformation mechanisms) factors, they are classified as EDC. We aimed to examine the potential endocrine-disrupting effects of phenylurea herbicides (phenuron, monuron, and diuron) on the oxytocin (OT) and arginine-vasopressin (AVP) release of neurohypophysis cell cultures (NH). In our experiments, monoamine-activated receptor functions of neurohypophyseal cells were used as a model. In vitro NH were prepared by enzymatic (trypsin, collagenase) and mechanical dissociation. In the experimental protocol, the basal levels of OT and AVP were determined as controls. Later, monoamine (epinephrine, norepinephrine, serotonin, histamine, and dopamine) activation (10−6 M, 30 min) and the effects of phenylurea (10−6 M, 60 min) alone and in combination (monoamines 10−6 M, 30 min + phenylureas 10−6 M, 60 min) with monoamine were studied. OT and AVP hormone contents in the supernatant media were measured by radioimmunoassay. The monoamine-activated receptor functions of neurohypophyseal cells were modified by the applied doses of phenuron, monuron, and diuron. It is concluded that the applied phenylurea herbicides are endocrine disruptor agents, at least in vitro for neurohypophysis function.